IMPROVING TRANSFER PRICING IN UKRAINE USING AMERICAN EXPERIENCE - Белей (Belei), Cвітлана (Svitlana); Melnychuk, Dmytro; Mykhalchyshyna, Larysa; Yevtushenko, Nataliia; Grinenko, Uliana (My University, 2021)
There is a need for additional research on the theory and practice of transfer pricing in Ukraine due to its rapid impact on the country's economy. The United States has the best experience in applying transfer pricing principles. Therefore, it is expedient to carry out research and theoretical systematization of problems of transfer pricing regulation on the basis of international and Ukrainian arbitration practices, aimed at identifying issues that need to be improved. This study aims to analyze and compare the experience of transfer pricing regulation to adapt best foreign practices. The comparison and sampling methods were used in the course of the research. The analytical study based on current regulatory and judicial practice and examples of tax dispute resolution in the United States and Ukraine. The results showed that the Ukrainian normative judicial practice is in the stages of establishment and needs further research. Analysis of statistical information shows that tax disputes in Ukraine focus on "technical errors" and the withdrawal of capitalto countries with low tax jurisdiction. In contrast, the United States, whose tax disputes focus on intra-corporate transactions.The research is based on the requirements of the fundamental documents of the Organization for Economic Cooperation and Development (OECD) and by the United Nations Tax Committee (UN), International Accounting Standards Board (IASB), Generally Accepted Accounting Principles (GAAP), as well as on statistical data obtained in the process of analysis of tax authority reporting.
Keywords: Transfer Price;Transfer Pricing;Arm’s Length Standard;Related Parties;Arbitration Practices;Controlled Operations;Regulation of Transfer Pricing;Multinational Companies;Implementation of Transfer Pricing